2015
DOI: 10.1007/s11103-015-0309-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FATTY ACID ELONGATION1 expression in embryonic and vascular tissues of Brassica napus

Abstract: The expression of the FATTY ACID ELONGATION1 genes was characterised to provide insight into the regulation of very long chain fatty acid (VLCFA) biosynthesis in Brassica napus embryos. Each of the two rapeseed homoeologous genes (Bn-FAE1.1 and Bn-FAE1.2) encoding isozymes of 3-keto-acylCoA synthase, a subunit of the cytoplasmic acyl-CoA elongase complex that controls the production of elongated fatty acids, are expressed predominantly in developing seeds. The proximal regions of the Bn-FAE1.1 and Bn-FAE1.2 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…In the current study, qRT-PCR analysis showed elevated levels of KCS1 transgene expression in two transgenic groundnut plants during drought-stress, compared to mock and wild type plants. Two transgenic groundnut plants showed over four folds increase in total wax content confirm that AhKCS1 expression enhanced wax biosynthesis and secretion pathways under drought stress, as described earlier in Arabidopsis (Todd et al, 1999), Brassica napus (Chiron et al, 2015), apple (Hao et al, 2017). In this context, higher expression of the AhKCS1 gene seems a better survival strategy under stress condition in transgenic groundnut plants.…”
Section: Discussionsupporting
confidence: 83%
“…In the current study, qRT-PCR analysis showed elevated levels of KCS1 transgene expression in two transgenic groundnut plants during drought-stress, compared to mock and wild type plants. Two transgenic groundnut plants showed over four folds increase in total wax content confirm that AhKCS1 expression enhanced wax biosynthesis and secretion pathways under drought stress, as described earlier in Arabidopsis (Todd et al, 1999), Brassica napus (Chiron et al, 2015), apple (Hao et al, 2017). In this context, higher expression of the AhKCS1 gene seems a better survival strategy under stress condition in transgenic groundnut plants.…”
Section: Discussionsupporting
confidence: 83%
“…The expression of HaKCS1 in developing seeds increases continuously until seeds reach 18 DAF, the point of maximal oil accumulation, suggesting it play a role in the synthesis of the VLCFAs present in sunflower oil. The expression of these genes resembles that reported previously for Brassica napus FAE1 elongase, which is responsible for the synthesis of erucic acid in this species, and that is mainly expressed in seeds but also in vegetative tissues (Chiron et al 2015). Indeed, the 20:0 and 22:0 fatty acids from sunflower oil were synthesized by enzymes involved in surface lipid production that were not specific for oil synthesis and accumulation.…”
Section: Tissue Specific Expression Of the Hakcs Genessupporting
confidence: 79%
“…Therefore, numerous efforts to modify the FA profile of total lipids (TLs, which include both polar and neural lipids) have been reported for higher plants (Ruiz-Lopez et al, 2013 and algae (Gong et al, 2014;Schuler et al, 2017). For example, the FA composition in TLs can be altered toward higher PUFA contents by engineering a number of desturases, elongases, and transcription factors (Chiron et al, 2015;Lee et al, 2016;Poliner et al, 2018). However, biosynthesis of ''designer TAG molecules,'' i.e., TAGs with a PUFA profile tailored for a particular nutritional value or health benefit, has not been reported so far from the potential feedstocks for PUFA-rich TAG.…”
Section: Molecular Plantmentioning
confidence: 99%